Penerapan Sanksi Pidana Terhadap Anggota Polri Yang Melakukan Penyalahgunaan Senjata Api - Manuhutu, Philicia; Alfons, Saartje Sarah; Latumaerissa, Denny (SANISA: Jurnal Kreativitas Mahasiswa Hukum, 2023)
Introduction: Normatively, Indonesia is actually a country that is quite strict in implementing the rules of gun ownership for civilians. There are a number of legal bases that regulate this, starting from the level of the Law, namely Emergency Law Number 12 of 1951, Law Number 8 of 1948 and PERPU Number 20 of 1960. The rest are regulations issued by the Police such as the Chief of Police Decree No. Skep/244/II/1999 and Chief of Police Decree No. 82 of 2004 concerning the Implementation of Supervision and Control of Non-Organic Weapons. In fact, the use of firearms must be very sensitive and selective, not in every condition of handling crimes the police must show, point and even pop their firearms. In Perkap 01 of 2009 concerning the purpose of the use of force in police actions Article 2 states: The purpose of the use of force in police actions is: prevent, inhibit, or stop the actions of criminals or suspects who are attempting or carrying out actions that are against the law; prevent criminals or suspects from escaping or taking actions that endanger members of the Police or the public; protect themselves or the public from the threat of acts or actions of criminals or suspects that can cause severe or deadly injuries; or protect the honor of decency or property of oneself or the community from attacks that are against rights and / or threaten human life. Various cases of shooting or misuse of firearms by members of the police have resulted in the public becoming victims.Purposes of the Research: This article aims to analyze and discuss law enforcement for members of the National Police in the misuse of firearms and analyze and discuss the application of criminal sanctions against members of the National Police who misuse firearms.Methods of the Research: Research methods used with normative juridical research type. The problem approach used is the legislation approach, the concept analysis approach, the case approach. Sources of legal materials used are primary legal materials and secondary legal materials. The collection technique is through literature studies and is further analyzed through the way of description using qualitative methods.Results of the Research: The results showed that in law enforcement against unscrupulous members of the National Police through the application of criminal sanctions in the misuse of firearms through efforts to overcome the misuse of firearms by members of the National Police are grouped into 2 groups, namely repressively and preventively. Repressively, against members of the Police who misuse firearms will be subject to action in the form of disciplinary sanctions and / or criminal sanctions as stipulated in the Criminal Code. Preventive efforts are carried out by tightening psychological tests and mental tests for the right to hold firearms, not allowing members with personal, family or official problems to borrow firearms, and retesting the right to hold firearms for Polri members who hold firearms. The application of criminal sanctions against unscrupulous members of the National Police who misuse firearms resulting in the death of members of the public based on the laws and regulations applicable to unscrupulous members of the National Police is legally processed through a trial process in court and based on the juridical and non-juridical legal considerations of the Judge so that the judge decided that the defendant Markus Manuhutu alias Max alias Maku was legally and convincingly proven guilty of committing a criminal act due to his negligence resulting in the death of another person in accordance with Article 359 of the Criminal Code and imposed a prison sentence on the defendant with a prison sentence of 2 (two) years and 6 (six) months.